2012
DOI: 10.1371/journal.pgen.1002882
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Regulatory Impact of Alternative Polyadenylation in Human B-Lymphoblastoid Cells

Abstract: Gene expression varies widely between individuals of a population, and regulatory change can underlie phenotypes of evolutionary and biomedical relevance. A key question in the field is how DNA sequence variants impact gene expression, with most mechanistic studies to date focused on the effects of genetic change on regulatory regions upstream of protein-coding sequence. By contrast, the role of RNA 3′-end processing in regulatory variation remains largely unknown, owing in part to the challenge of identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 71 publications
4
67
0
Order By: Relevance
“…Moreover, an association with expression divergence held also for repeats in other genic regions. The strongest of them was evident for 3 ′ UTRs, consistent with their known role in gene regulation (Yoon et al 2012). In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, an association with expression divergence held also for repeats in other genic regions. The strongest of them was evident for 3 ′ UTRs, consistent with their known role in gene regulation (Yoon et al 2012). In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns.…”
Section: Discussionsupporting
confidence: 57%
“…Loss or gain of miRNA-mediated regulation of mRNAs has been proposed to link changes in APA with altered gene output 63 . Consistent with this proposal, regulatory cis -acting elements, including miRNA-binding sites, are enriched between proximal and distal polyadenylation sites 45 . In a GWAS using HapMap data across multiple populations, SNVs that shortened the mRNA 3′ UTR and caused a loss of miRNA-binding target sites were associated with increased gene expression 63 .…”
Section: Variants Affect Mirna-mediated Regulationsupporting
confidence: 53%
“…A notable example involves susceptibility to facioscapulohumeral muscular dystrophy (FSHD), in which individual differences in the polyadenylation hexanucleotide sequence of the last exon of double homeobox 4 ( DUX4 ) are determinative for disease (BOX 2). Analysis of allele-specific expression in LCLs from six individuals revealed that variants within the hexanucleotide are significantly more likely to have an effect on gene expression than variants in the rest of the 3′ UTR, and that single-nucleotide substitutions are sufficient to change the use of distal versus proximal poly adenylation sites 45 . A detailed analysis of blood samples from 94 individuals to find SNVs in linkage disequilibrium with a change in polyadenylation site usage identified 5 top candidates, all of which were in the AATAAA motif.…”
Section: Impact Of Genetic Variation On Mrna 3′ Endsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across different tissue samples, we observed that about twothirds of multi-UTR genes show significant differences in usage of the first pA sites and thus can potentially escape post-transcriptional regulation. There is a higher frequency of noncanonical hexamer signals at the proximal pA sites of multi-UTR genes than in single-UTR genes, and these noncanonical signals were shown to be weaker pA sites (Wickens and Stephenson 1984;Yoon et al 2012). However, the 39 UTRs of pAM genes are more highly conserved, their distal UTR regions are enriched for miRNA-binding sites, and the regions surrounding their proximal pA signals are more conserved relative to NpAM genes.…”
Section: Discussionmentioning
confidence: 96%